Inapproriate prescription of cough remedies among children hospitalized with respiratory illness over the period 2002 to 2015 in Kenya - Maina, M; Akech, S; Mwaniki, P; Gachau, S; Ogero, M; Julius, T; Irimu, G; English, M (Wiley, 2016)
Objective To examine trends in prescription of cough medicines over the period 2002 to 2015 in children aged 1 month to 12 years admitted to Kenyan hospitals with cough, difficulty breathing or diagnosed with a respiratory tract infection. Methods We reviewed hospitalization records of children included in four studies providing cross-sectional prevalence estimates from government hospitals for 6 time periods between 2002 and 2015. Children with an atopic illness were excluded. Amongst eligible children, we determined the proportion prescribed any adjuvant medication for cough. Active ingredients in these medicines were often multiple and were classified into five categories: antihistamines, antitussives, mucolytics/expectorants, decongestants and bronchodilators. From late 2006, guidelines discouraging cough medicine use have been widely disseminated and in 2009 national directives to decrease cough medicine use were issued. Results Across the studies, 17,963 children were eligible. Their median age and length of hospital stay were comparable. The proportion of children who received cough medicines shrank across the surveys: approximately 6% [95% CI 5.4,6.6] of children had a prescription in 2015 vs. 40% [95% CI 35.5,45.6] in 2002. The most common active ingredients were antihistamines and bronchodilators. The relative proportion that included antihistamines has increased over time. Conclusions There has been an overall decline in the use of cough medicines among hospitalized children over time. This decline has been associated with educational, policy and mass media interventions.